2022
DOI: 10.1039/d1ma00931a
|View full text |Cite
|
Sign up to set email alerts
|

External complexation of BODIPYs by CB[7] improves in-cell fluorescence imaging

Abstract: The nonradiative decay processes of BODIPYs can be considerably prevented by complexation with CB[7] to making utmost absorbed excitation energy used for high emission which plays a crucial role in fluorescence labelling and optoelectronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Consequently, the side effects associated with PDT therapy are minimized. 94 In antitumor therapy, a desired characteristic of chemical therapeutic agents is their accumulation and retention by the malignant cells. A supramolecular nanomedicine having a potential of conversion to "microfiber" intracellularly was developed by Sun et al where Phe-Phe-Val-Leu-Lyscamptothecin conjugates and CB [7] form supramolecularpeptide nanodrug (FFVLK-CPT, PC) through noncovalent interactions.…”
Section: Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the side effects associated with PDT therapy are minimized. 94 In antitumor therapy, a desired characteristic of chemical therapeutic agents is their accumulation and retention by the malignant cells. A supramolecular nanomedicine having a potential of conversion to "microfiber" intracellularly was developed by Sun et al where Phe-Phe-Val-Leu-Lyscamptothecin conjugates and CB [7] form supramolecularpeptide nanodrug (FFVLK-CPT, PC) through noncovalent interactions.…”
Section: Therapeuticsmentioning
confidence: 99%
“…This supramolecular PS complex demonstrated enhanced ROS generation effectiveness along with significant self-degradation property after the PDT treatment. Consequently, the side effects associated with PDT therapy are minimized . In antitumor therapy, a desired characteristic of chemical therapeutic agents is their accumulation and retention by the malignant cells.…”
Section: Use Of Cb[n] In Photodynamic Therapeuticsmentioning
confidence: 99%
“…One class of compounds that has gained significant interest in the field of supramolecular synthesis is boron dipyrromethene (BODIPY), a highly fluorescent chromophore known for its excellent photophysical properties . BODIPY derivatives have been widely used in a range of applications, including bioimaging, sensing, and optoelectronics. However, controlling the assembly and organization of BODIPY molecules is crucial to achieve desired properties and functions in these materials. …”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53] BODIPY scaffolds can be easily functionalized at several sites to construct ordered materials with predetermined structures and properties, which are used in widespread applications in fields such as fluorescence imaging and sensing, dye sensitized solar cells, photocatalysis, singlet oxygen generation and photodynamic therapy. [54][55][56][57][58][59] Recently, others and we have demonstrated the selfassembly of various BODIPY derivatives through diverse methodologies. [60][61][62][63][64][65][66][67] As these studies revealed, particularly, XB interactions are a useful tool to modulate the supramolecular assembly and the resulting electronic, optical, and mechanical properties of BODIPYs.…”
Section: Introductionmentioning
confidence: 99%
“…BODIPY scaffolds can be easily functionalized at several sites to construct ordered materials with predetermined structures and properties, which are used in widespread applications in fields such as fluorescence imaging and sensing, dye sensitized solar cells, photocatalysis, singlet oxygen generation and photodynamic therapy. 54–59…”
Section: Introductionmentioning
confidence: 99%